Multi-objective optimization of a multi-step solar-driven Brayton plant. (15th July 2015) - Sánchez-Orgaz, S.; Pedemonte, M.; Ezzatti, P.; Curto-Risso, P.L.; Medina, A.; Calvo Hernández, A.
Highlights: A multi-objective multi-parametric optimization study of a Brayton multi-step thermosolar plant is presented. Each subsystem is modelled (solar collector, gas turbine) including the main irreversibility sources in this kind of plants. The Pareto Fronts are obtained by using a genetic algorithm and also from exact calculations. Two objective functions are simultaneously optimized: the overall plant efficiency and the power output. Abstract: A multi-objective and multi-parametric optimization analysis is presented for a recuperative multi-step solar-driven Brayton thermosolar plant. The analysis is done over a thermodynamic analytical model that incorporates all the losses observed in real plants, from the heat engine itself and from the solar subsystem. The model allows to consider several compression–expansion stages. The overall system efficiency and the power output were taken as objective functions. The Pareto Front of the system is obtained by considering possible fluctuations in all the involved parameters. This study allows to discern the significant design variables. Then, the exact Pareto Fronts were calculated, by taking as variables only those parameters, and building an appropriate grid. Several configurations (ideal and realistic, with single stage or multi-step compression–expansion processes) were analyzed and multi-criteria decision making procedures applied in order to obtain physical insights from the results. It was shown the importance of electing an appropriate conducting gas, and adequate values of the global pressure and temperature ratios. This study could constitute an interesting guideline for the design of future generations of plants of this type, that are now at the research and developing stage.